Type I Interferon Induced by Streptococcus suis Serotype 2 is Strain-Dependent and May Be Beneficial for Host Survival - Auger, Jean-Philippe; Santinón, Agustina; Roy, David; Mossman, Karen; Xu, Jianguo; Segura, Mariela; Gottschalk, Marcelo (Frontiers in Immunology, 2017)
Streptococcus suis serotype 2 is an important porcine bacterial pathogen and emerging zoonotic agent mainly responsible for sudden death, septic shock, and meningitis, with exacerbated inflammation being a hallmark of the infection. However, serotype 2 strains are genotypically and phenotypically heterogeneous, being composed of a multitude of sequence types (ST) whose virulence greatly varies: the virulent ST1 (Eurasia), highly virulent ST7 (responsible for the human outbreaks in China), and intermediate virulent ST25 (North America) are the most important worldwide. Even though type I interferons (IFNs) are traditionally associated with important anti-viral functions, recent studies have demonstrated that they may also play an important role during infections with extracellular bacteria. Upregulation of IFN-β levels was previously observed in mice following infection with this pathogen. Consequently, the implication of IFN-β in the S. suis serotype 2 pathogenesis, which has always been considered a strict extracellular bacterium, was evaluated using strains of varying virulence. This study demonstrates that intermediate virulent strains are significantly more susceptible to phagocytosis than virulent strains. Hence, subsequent localization of these strains within the phagosome results in recognition of bacterial nucleic acids by Toll-like receptors 7 and 9, leading to activation of the interferon regulatory factors 1, 3, and 7 and production of IFN β. Type I IFN, whose implication depends on the virulence level of the S. suis strain, is involved in host defense by participating in the modulation of systemic inflammation, which is responsible for the clearance of blood bacterial burden. As such, when induced by intermediate, and to a lesser extent, virulent S. suis strains, type I IFN plays a beneficial role in host survival. The highly virulent ST7 strain, however, hastily induces a septic shock that cannot be controlled by type I IFN, leading to rapid death of the host. A better understanding of the underlying mechanisms involved in the control of inflammation and subsequent bacterial burden could help to develop control measures for this important porcine and zoonotic agent.